The emerald handbook of fintech: Reshaping finance - banker, H. Kent; Filbeck, Greg; Black, Keith (United Kingdom Emerald Publishing, 2024)
The rapidly growing fintech market reflects new technology that seeks to improve and automate the delivery and use of financial services. Regulation changes have provided new opportunities in crowdfunding and peer-to-peer (P2P) lending. At the same time, technological advances have made artificial intelligence (AI) and machine learning (ML) accessible to practitioners without a programming background. New markets in cryptocurrencies and digital assets promise to make finance more global with lower transaction costs and faster transaction processing times.